ANALYSIS OF THE IMPLEMENTATION OF DSN-MUI FATWA NO. 44/DSN–MUI/2004 ON THE IJĀRAH CONTRACT IN MULTISERVICE FINANCING AT ISLAMIC FINANCIAL INSTITUTIONS: A Case Study of BPRS Artha Fisabilillah Cianjur - Mas Atiawati; Ibdalsyah Ibdalsyah; Hari Susanto; Haris Renaldi (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
The increasing complexity of economic activities requires financing instruments that are not only responsive to public needs but also compliant with Islamic principles. One such instrument offered by Islamic financial institutions is multi-service financing based on the ijarah contract. However, improper implementation may lead to deviations from sharia principles, particularly the risk of riba. This study aims to analyze the implementation of the ijarah contract in multi-service financing at BPRS Artha Fisabilillah Cianjur, examine its conformity with the DSN-MUI Fatwa Number 44 of 2004, and identify potential indications of non-sharia practices. This research employs a qualitative field research approach. Data were collected through observation, interviews, and documentation, using both primary and secondary sources. The data were analyzed using descriptive qualitative methods. The findings indicate that the implementation of ijarah-based multi-service financing at BPRS Artha Fisabilillah has complied with the provisions stipulated in DSN-MUI Fatwa Number 44 of 2004, particularly regarding the object of the contract and the determination of ujrah. Therefore, the financing practice can be considered sharia-compliant and free from elements of riba.